FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN NON KEUANGAN GO PUBLIC TAHUN 2004-2013 - Sari, Wahyuni Rusliyana (Manajemen Bisnis Kompetensi, 2017)
ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ ÃÂ  ABSTRACTThe problem of this research was the influence of dividend per share, earnings per share, book value, dividend payout ratio, price earnings ratio and size toward market price. The objective of this research was to identify the factors that influence the market price of firms listed in Indonesian Stock Exchange over the period 2004-2013. The methodology of this research was non-linier multiple regression (log-lin model) with Ordinary Least Squares (OLS) analysis which is test is done by classic assumption. Sample in this research is 25 non-financial companies from seven sectors they are agriculture, mining, basic& chemical industries, consumer goods, property& construction, infrastructure utilities& transportation. Finding and contribution this research was earnings per share, book value, price earnings ratio and size have influence toward market price significant at 5% probability level. Other independent variables they are dividend per share and dividend payout ratio do not have influence toward market price. Research limitation or implication in this research was to financial manager used the information that earnings per share, book value, price earnings ratio and size have influence toward market price than increasing company performance. As for investors it is used as a reference before investing that is not the distribution of the dividend will increase the stock price.Keyword: Book value, Dividend payout ratio, Dividend per share, Earnings per share, Market price, Price earnings ratio and Size.